Chemical structure and antiviral activity of the sulfated heterorhamnan isolated from the green seaweed Gayralia oxysperma - Cassolato, Juliana E. F. (2008)
A homogeneous sulfated heterorhamnan was obtained by aqueous extraction, then by ultrafiltration from the green seaweed Gayralia oxysperma. Besides α-l-rhamnose it contains glucuronic and galacturonic acids, xylose and glucose. The structure was established by methylation analyses of the carboxyl-reduced, carboxyl-reduced/desulfated, carboxyl-reduced/Smith-degraded, and carboxyl-reduced/Smith-degraded/desulfated products and 1D, 2D NMR spectroscopy analyses. The heterorhamnan backbone is constituted by 3- and 2-linked rhamnosyl units (1.00:0.80), the latter being ∼50% substituted at C-3 by side chains containing 2-sulfated glucuronic and galacturonic acids and xylosyl units. The 3- and 2-linked rhamnosyl units are unsulfated (20%), disulfated (16%), and mostly monosulfated at C-2 (27%) and C-4 (37%). The branched and sulfated heterorhamnan had high and specific activity against herpes simplex virus.